Revitalisasi Peran Kepemudaan Melalui Karang Taruna Dalam Pengelolaan Sampah Plastik di Desa Baros, Kabupaten Serang - Cahyani, Intan Putri; Darmastuti, Shanti; Afrimadona; Ali, Syarif (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2022)
Baros Village, Serang Regency has a strategic geographical location, but there are still various closely related environmental and community problems, namely waste. This is where the role of youth in plastic waste management is needed. Through several stages, the service team seeks to revitalize the youth role of the Baros Village Youth Organization through various and participatory initiatives in maintaining, maintaining, and improving environmental functions through plastic waste management. The Participatory Rural Appraisal model is used in this activity with considerations from problem identification until later at the completion stage, all involving partners. The counseling activities carried out are expected to provide a stimulus for Karang Taruna members to carry out plastic waste management activities that have economic benefits as well as a pilot project to increase the role of youth in village development. Although the counseling activity was carried out within limitations due to the Covid-19 Pandemic, the enthusiasm of Karang Taruna members who took part in this activity to become a driving force for waste management efforts in the Baros Village environment was very high.